Organizational Culture-Based Strategy for Enhancing Human Resource Performance - Jaya, Lukman (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
To be able to manage an organization properly, a clear understanding and attention to organizational culture is required, in accordance with the context of empowering human resources, in order to produce professional employees with high integrity. The purpose of this research is to find out the strategies to improve HR performance based on organizational culture at PT. Box Design Megahindo South Jakarta. This research uses qualitative method. Data were collected by observation, interviews and methods of focus group discussion then analyzed by SWOT method. The result of this research is the condition of organizational culture at PT. Kotak Design Megahindo that currently uses a 4K organizational culture. The organizational culture that is applied tends to bring excess value to the team when working between them